A COMPREHENSIVE ANALYSIS OF THE IMPACT OF GLOBALIZATION ON AUDITING STANDARDS - Abduhamidov Abdurahmon Abdulatif o‘g‘li, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article examines the profound impact of globalization on auditing standards, unraveling the complexities faced by auditors in an increasingly interconnected global economy. As businesses extend their operations across borders, auditors grapple with diverse regulatory frameworks, cultural nuances, and evolving business practices. The literature review reveals a compelling narrative, highlighting the imperative for harmonized auditing standards in the face of globalization. The International Auditing and Assurance Standards Board (IAASB) plays a pivotal role in formulating and updating standards to align with the intricacies of a borderless economy. Technological advancements, particularly in data analytics and artificial intelligence, are transforming audit methodologies, enhancing efficiency, and addressing global financial challenges. Challenges emerge in adapting to local variations, requiring auditors to strike a delicate balance between standardization and cultural adaptability. Collaboration and communication among auditors, regulators, and standard-setting bodies emerge as critical elements for success in this dynamic global auditing landscape.